TRLS-01. Trial in Progress: A Prospective, Multicenter Phase 2b Study to Establish Image Interpretation Criteria for 18F-Fluciclovine PET in Detecting Recurrent Brain Metastases after Radiation Therapy (PURSUE). (9th August 2021) - Kotecha, Rupesh; Chaglassian, Alain; Tainer, Nancy; Teoh, Eugene
Abstract: Background: Brain metastases are the most common intracranial tumor in adults, occurring in 10–40% of patients with cancer. Despite multimodal treatment approaches, the prognosis remains poor and post-treatment follow-up with conventional MRI (CE-T1-weighted and FLAIR/T2-weighted) of the brain is recommended to monitor for disease recurrence. However, owing to the similar appearance of treatment-related changes like radiation necrosis with that of true recurrence, conventional MRI has low specificity. Given the high mortality of patients with brain metastases and the considerable treatment-associated morbidity, a need remains for an imaging modality that accurately differentiates recurrence from treatment-related changes. Accurate imaging could help physicians identify patients for whom non-effective or unneeded treatments can be ceased in order to minimize treatment-associated morbidity, and to avoid erroneous premature cessation of potentially effective therapy. 18 F-Fluciclovine is a synthetic amino acid-based PET imaging agent that has potential to evaluate primary and metastatic brain cancers owing to its low normal background uptake in the brain and increased uptake in brain tumors. Methods: NCT04410367 is a prospective, open-label, single-arm, single-dose (185 MBq ± 20%) study with a primary objective to establish visual image interpretation criteria for 18F-fluciclovine PET studies of recurrent brain metastases. Forty subjects with solid tumor brain metastases who have undergone radiation therapy will be enrolled across 8 US sites if they have a reference lesion considered equivocal on MRI for recurrent brain metastasis and are planned for craniotomy. Subjects will undergo 18F-fluciclovine PET <28 days after the equivocal MRI and 2–21 days before planned craniotomy. Outcome measures comprise diagnostic performance of 18F-fluciclovine PET at different thresholds of 18F-fluciclovine uptake compared with histopathology, subject- and lesion-level diagnostic performance based on application of the established image interpretation criteria, and safety evaluations. Enrolment began in August 2020 and the trial is open at the time of submission.